EVALUATION OF METEOROLOGICAL FACTORS INFLUENCE ON BENZENE ACCIDENTAL POLLUTION. CASE STUDY: BACAU CITY 2008 - DOINA CAPSA; VALENTIN NEDEFF; NARCIS BARSAN; EMILIAN MOSNEGUTU; DANA CHITIMUS (Journal of Engineering Studies and Research, 2017)
Air quality depends on the type and size of industrial activities, traffic intensity, municipal and industrial waste management etc. In addition, air quality in urban areas depends by the green areas management, population density, climatic conditions and geographic. This paper study the correlations between the most important meteorological factors, humidity, temperature, wind and benzene accidental pollution, with influence on pollutant dispersion (related to 2008). The correlation were performed by taken in to considerations the accidental benzene pollution recorded in 2008 in Bacau City and meteorological factor recorded at the regional meteorological station.